2007
DOI: 10.1002/eji.200636421
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of IL‐6 trans‐signaling mechanisms controlling L‐selectin adhesion by fever‐range thermal stress

Abstract: Fever is associated with improved survival during infection in endothermic and ectothermic species although the protective mechanisms are largely undefined. Previous studies indicate that fever-range thermal stress increases the binding activity of the L-selectin homing receptor in human or mouse leukocytes, thereby promoting trafficking to lymphoid tissues across high endothelial venules (HEV). Here, we examined the evolutionary conservation of thermal regulation of L-selectin-like adhesion. Leukocytes from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…Thus, IL-6 is obligatory for thermally-induced increases in L-selectin binding activity in lymphocytes as well as enhanced intravascular display of ICAM-1 in HEVs [40,69,73,78]. Other proinflammatory cytokines that are more often recognized for the regulation of lymphocyte-endothelial adhesion such as TNF, IL-1b, IFN-are not necessary for the response to feverrange thermal stress [40,78].…”
Section: Limited Leukocyte Interactions With Tumor Vessels Under Steamentioning
confidence: 92%
See 3 more Smart Citations
“…Thus, IL-6 is obligatory for thermally-induced increases in L-selectin binding activity in lymphocytes as well as enhanced intravascular display of ICAM-1 in HEVs [40,69,73,78]. Other proinflammatory cytokines that are more often recognized for the regulation of lymphocyte-endothelial adhesion such as TNF, IL-1b, IFN-are not necessary for the response to feverrange thermal stress [40,78].…”
Section: Limited Leukocyte Interactions With Tumor Vessels Under Steamentioning
confidence: 92%
“…In addition, these mechanisms represent independent, but complementary responses in both lymphocytes and high endothelial cells that line HEVs. Temperatures that mimic febrile episodes (38-40 C) were shown to act directly on T and B lymphocytes to enhance the avidity and/or affinity of two lymphocyte homing molecules, L-selectin and 4 b 7 integrin [69,[73][74][75][76][77][78]. These molecules are obligatory for the initial tethering and rolling of lymphocytes along the luminal surface of HEVs in lymph nodes (Figure 1) or Peyer patches, a requisite first step in the adhesion cascade that ultimately directs lymphocytes into the underlying parenchymal tissue.…”
Section: Limited Leukocyte Interactions With Tumor Vessels Under Steamentioning
confidence: 99%
See 2 more Smart Citations
“…Solid organs harvested for transplantation may be stored at more extreme hypothermia for prolonged periods prior to transplant. Work from our group and others has shown that modest changes in temperature within the physiological range alters expression level of certain genes with important physiologic and clinical consequences (Cahill et al 1996;Chen et al 1997Chen et al , 2006Chen et al , 2009Wang et al 1998;Jiang et al 1999aJiang et al ,b, 2000Fairchild et al 2000;Singh et al 2000Singh et al , 2002Singh et al , 2008Hasday et al 2003;Ellis et al 2005;Appenheimer et al 2007;Vardam et al 2007;McClung et al 2008;Nagarsekar et al 2008Nagarsekar et al , 2012Cooper et al 2010a,b;Lipke et al 2010Lipke et al , 2011Fisher et al 2011;Maity et al 2011;Tulapurkar et al 2011Tulapurkar et al , 2012Zhang et al 2012;Gupta et al 2013). Most of the studies of temperature-dependent gene expression have focused on transcriptional regulation (Cahill et al 1996(Cahill et al , 1997Chen et al 1997;Singh et al 2008;Cooper et al 2010a,b;Maity et al 2011;Zhang et al 2012), but post-transcriptional regulation by small noncoding RNAs like microRNA (miRNA) may be as important as transcriptional regulation for ∼30% of all genes (Lewis et al 2005).…”
Section: Introductionmentioning
confidence: 99%